Time to Full Enteral Feeding for Very Low‐Birth‐Weight Infants Varies Markedly Among Hospitals Worldwide But May Not Be Associated With Incidence of Necrotizing Enterocolitis: The NEOMUNE‐NeoNutriNet Cohort Study. Issue 5 (22nd November 2018) - de Waard, Marita; Li, Yanqi; Zhu, Yanna; Ayede, Adejumoke I.; Berrington, Janet; Bloomfield, Frank H.; Busari, Olubunmi O.; Cormack, Barbara E.; Embleton, Nicholas D.; van Goudoever, Johannes B.; Greisen, Gorm; He, Zhongqian; et al.
Abstract: Background: Transition to enteral feeding is difficult for very low‐birth‐weight (VLBW; ≤1500 g) infants, and optimal nutrition is important for clinical outcomes. Method: Data on feeding practices and short‐term clinical outcomes (growth, necrotizing enterocolitis [NEC], mortality) in VLBW infants were collected from 13 neonatal intensive care units (NICUs) in 5 continents (n = 2947). Specifically, 5 NICUs in Guangdong province in China (GD), mainly using formula feeding and slow feeding advancement (n = 1366), were compared with the remaining NICUs (non‐GD, n = 1581, Oceania, Europe, United States, Taiwan, Africa) using mainly human milk with faster advancement rates. Results: Across NICUs, large differences were observed for time to reach full enteral feeding (TFF; 8–33 days), weight gain (5.0–14.6 g/kg/day), ∆ z ‐scores (−0.54 to −1.64), incidence of NEC (1%–13%), and mortality (1%–18%). Adjusted for gestational age, GD units had longer TFF (26 vs 11 days), lower weight gain (8.7 vs 10.9 g/kg/day), and more days on antibiotics (17 vs 11 days; all P < .001) than non‐GD units, but NEC incidence and mortality were similar. Conclusion: Feeding practices for VLBW infants vary markedly around the world. Use of formula and long TFF in South China was associated with more use of antibiotics and slower weight gain, but apparently not with more NEC or higher mortality. Both infant‐ and hospital‐related factors influence feeding practices for preterm infants. Multicenter, randomized controlled trials are required to identify the optimal feeding strategy during the first weeks of life. Abstract :